Micro/nano devices for blood analysis - Lima, Rui Alberto Madeira Macedo (2019)
[Excerpt] The development of microdevices for blood analysis is an interdisciplinary subject that demandsan integration of several research fields such as biotechnology, medicine, chemistry, informatics, optics,electronics, mechanics, and micro/nanotechnologies.Over the last few decades, there has been a notably fast development in the miniaturization ofmechanical microdevices, later known as microelectromechanical systems (MEMS), which combineelectrical and mechanical components at a microscale level. The integration of microflow and opticalcomponents in MEMS microdevices, as well as the development of micropumps and microvalves,have promoted the interest of several research fields dealing with fluid flow and transport phenomenahappening at microscale devices. [...]